DETERMINAN KELUHAN GANGGUAN KULIT PADA PEMULUNG SAMPAH DI TPA KELURAHAN TERJUN KECAMATAN MEDAN MARELAN TAHUN 2019 - Famita Rawati Siboro (JURNAL KESMAS DAN GIZI (JKG), 2019)
Skin disease is a disease related to the environment and human behavior. The incidence of skin diseases has increased because the cause of the disease is alive and breeding in landfills and poor waste collection. This is based on the environment of scavenger workers who have materials that can cause various kinds of skin disorders. Based on the results of preliminary surveys that have been carried out, the number of scavengers in the final disposal site of Kelurahan Falls is 75 people with different age characteristics, different levels of education and length of work. The problem at TPA Falls is work behavior on waste pickers. From observations from the field observations found that the scavenger working conditions in the garbage dump in the Kelurahan Falls generally suffer from skin disorders due to personal hygiene (skin, foot, nail and hand hygiene) which are not given enough attention and the use of Personal Protective Equipment (PPE) that is incorrect and incomplete. The purpose of this study was to determine knowledge, attitudes, actions to use personal protective equipment (PPE) and habits of personal hygiene, length of work, as well as the distance of the house from the landfill with complaints of skin disorders in the garbage scavengers in the TPA Kelurahan Falls. The research method is cross sectional which was analyzed using the Chi-Square test. The research location was conducted at TPA Kelurahan Terjun, Medan Marelan Subdistrict and was conducted in February and March 2019. 75 respondents were taken using simple random sampling technique. The research instrument was in the form of a questionnaire. The results of the study are variables that are not related to complaints of skin disorders that is length of work (P value = 0.617), while variables related to complaints of skin disorders are distance of residents' homes (P value = 0,000), non-compliance using PPE (P value = 0,000) do personal hygiene (P value = 0,000). Suggestions for scavengers to behave more clean and healthy life by maintaining health, personal hygiene and the environment, and using personal protection that must be worn at work.